2016
DOI: 10.33050/cices.v2i2.221
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Issues Of Economic Development Of Border Area Of Indonesia - Malaysia

Abstract: On the land, Indonesia is bordered by three countries: Malaysia, Papua New Guinea and Timor Leste.Whereas, in Indonesia sea area bordered by 10 countries: India, Malaysia, Singapore, Thailand,Vietnam, Philippines, the Republic of Palau, Australia, East Timor and Papua New Guinea. Most ofthe border region in Indonesia is still an underdeveloped area with less facilities and infrastructure ofsocial and economic. Formulation of the problem are: 1. How do the condition of the socio-economicand culture in the borde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…In fact, in many developing regions, cross-border entrepreneurship, including cross-border informal trade, has been regarded as one of the mechanisms to develop economic growth of the local community (Aralas et al, 2017;Bariyah et al, 2012). Nevertheless, many previous researches highlighted several common strategic issues pertaining cross-border entrepreneurship in Malaysia, including socioeconomic vulnerability, security, ethnic relations, and business practice differences (Awang et al, 2013;Sunarya & Sudaryono, 2016;Thai & Turkina, 2014). For example, the Malaysia-Indonesia border in the Sarawak-Kalimantan region, faced myriad of issues, and became socio-politically vulnerable, that led to border conflicts between Malaysia and Indonesia.…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, in many developing regions, cross-border entrepreneurship, including cross-border informal trade, has been regarded as one of the mechanisms to develop economic growth of the local community (Aralas et al, 2017;Bariyah et al, 2012). Nevertheless, many previous researches highlighted several common strategic issues pertaining cross-border entrepreneurship in Malaysia, including socioeconomic vulnerability, security, ethnic relations, and business practice differences (Awang et al, 2013;Sunarya & Sudaryono, 2016;Thai & Turkina, 2014). For example, the Malaysia-Indonesia border in the Sarawak-Kalimantan region, faced myriad of issues, and became socio-politically vulnerable, that led to border conflicts between Malaysia and Indonesia.…”
Section: Problem Statementmentioning
confidence: 99%
“…It is crucial to understand how entrepreneurial activities in the border villages take place regardless of the absence of formal rules imposed. In addition, it is found that study on entrepreneurship in the small remote border areas, especially the informal cross-border trade receives less attention compared to developed areas (Ngah, 2012;Sunarya & Sudaryono, 2016)…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…State apparatus at the border must be complicated to carry out regular surveillance and anticipate the complexity of problems that exist at the border, including border disputes, terrorism, illegal immigrants, illegal logging, illegal fishing, smuggling of goods and illegal drugs, penetration of foreign ideologies and various other forms of violations that threaten state sovereignty (Bennett, 2018;Rusmiyati et al, 2022;Wilcox et al, 2021). Besides that, most border areas in Indonesia are underdeveloped areas with minimal facilities in social and economic aspects (Cecilia, 2021;Sunarya & Sudaryono, 2016).Realizing that, since the beginning of President Joko Widodo's administration, he has raised the border issue as one of the main issues in the direction of national development policy where one of the points is "Building Indonesia from the Periphery. "This point has been implemented in several policies to address complex problems at the border.…”
Section: Introductionmentioning
confidence: 99%